Role of inorganic and organic ions in response to salt and drought stresses - Ghaffari, Akram (Journal of Plant Stress Physiology, 2022)
Plants have different responses to salt and drought stresses. They transport several ions to balance osmotic potential and stomatal closure and opening. Ions including inorganic and organic cations and anions play a crucial role to alleviate abiotic stresses (salt and drought). Inorganic cations containing Na+, K+, Mg2+ and Ca2+ and inorganic anions comprising Cl-, PO42-, NO3-, SO42- have a great role in osmotic and ion hemostasis in response to salt and water stresses. Organic anions like acetate, succinate, malate, citrate and oxalate showed vital impacts on alleviating damages of drought and salt stresses that lead to higher yield in severe conditions. In order to recognize the mechanisms that increase tolerance of salt and drought stresses, this review illustrates roles of organic and inorganic anions and cations and their interactions on osmotic adjustment, stomata closure and ion hemostasis. Halophytes will be compared with glycophytes as the proper models to find out differences in stress tolerance mechanisms.